PERANCANGAN KOMUNIKASI VISUAL PRANGKO SERI PAHLAWAN NASIONAL PROVINSI SUMATERA BARAT - SYAVIA SARI YULHIJRA, Drs. Muzni Ramanto, Yofita Sandra, S.Pd, M.Pd (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
West Sumatera has many born a big heroes from other side like at defend direction, religius, education, art and culture. Because so many people that did know about ad did not known about of heroes National of west Sumatera and then needed a thing to remember of work them to country and state. The purpose of this script is (1) to design letter as thing of filately that imagine a paint about National heroes from west Sumatera (2) for more be introduce back to people heroes from west Sunatera, they are it depend our country, and as filately thing to letter fan. And method that used in this design is analize method 5 W + 1 H is, what, where, when, who, why and how. The heroes is, Abdul Muis, Agus Salim, Bagindo Aziz Chan, Buya Hamka, Ilyas Yacuob,Moh Hatta, Mohammad Nasir, Muhammad Yamin, Rasuna Said, Rohana Kudus, Sultan Syahril, Tan Malaka, Tuanku Imam Bonjol. Keyword : Mail stamp, Heroes, West Sumatera